Studi Literatur Review: Kemampuan Pembuktian Matematis Mahasiswa - Fitriani Fitriani; Rusi Ulfa Hasanah; Saprina Maulida (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to comprehensively examine students’ mathematical proof abilities, including the factors that influence them and the efforts that can be made to improve these abilities. The method used in this study is a systematic literature review by analyzing various related research articles published in reputable scientific journals such as Springer Link and Semanthic Scholar. The results of the study show that students’ mathematical proof abilities are still relatively low, influenced by various factors such as conceptual understanding, reasoning ability, and experience in constructing proof. Several ways that can be done to improve students’ mathematical proof skills include developing teaching materials, implementing learning models that encourage proof activities, and providing systematic training and feedback. This study provides important implications for the development of mathematics learning in higher education, especially in efforts to improve students’ mathematical proof skills.